From Empire to Colony: The Halifax Cholera Outbreaks of 1834 and 1866 - Fowler, Madeline (Acadiensis, 2018)
This article explores the relationship between emigration and outbreaks of cholera in Halifax between 1832 and 1866. Pressures associated with migration from the British Isles, as well as the threat and reality of transmittable diseases like cholera, reveal the vulnerability and strains felt as a colonial port town located off the North Atlantic. This article presents the struggles and tensions apparent with managing emigrants, many of which were bound for territory beyond Nova Scotia, and contributes not only to the historical understanding of how cholera was dealt with in Halifax but also provides a unique perspective on understanding the greater struggles of 19th-century colonial life.